Metrics for the emissions of F-gas refrigerants - Miranda, ND; Palafox-Alcantar, PG; Khosla, R; McCulloch, M (Elsevier, 2023)
This paper examines the metrics used to account for the contribution to global warming from fluorinated gases (f-gases) mainly used as refrigerants for cooling. F-gases are key to climate mitigation discussion as they a) are critical to delivering the surging demand for air conditioners which is expected to triple by 2050, b) have strong Global Warming Potential (GWP) as high as 12,000 kgCO2-eq (for e.g., HFC-23) and c) are targeted by international policy agreements such as the Montreal Protocol and Kigali Amendment. F-gases exacerbate atmospheric warming when leaked from cooling equipment, or during other phases of their life cycle. Thus far, the way these gases impact global warming is mostly reported based on their CO2-equivalent emissions with a time horizon of 100 years. However, the problem is that f-gases have significantly different lifespans and the GWP100 does not account for these variations. The debate on metrics to account for warming of other short-lived climate pollutants (SLCP), such as methane is already ongoing. Here, we provide the first step to open such debate for short-lived f-gases. We address this, first, with a critical review of the available metrics for carbon foot-printing of f-gases and present a gap analysis between the existing carbon foot printing metrics and the need to better understand warming from f-gases. Second, we use an atmospheric model to illustrate how the incumbent metric (CO2-equivalent calculated using GWP100), misrepresent the warming of an exemplary f-gas refrigerant (HFC-134a). The model outputs novel profiles of atmospheric concentration, radiative forcing, and temperature, in three scenarios. Scenario A models the response to a positive step change in emissions of the HFC, while Scenario B is the inverse. Scenario C models a reduction of 85% by 2036 of emissions according to targets for high-emitting countries set in the Kigali Amendment. The modelling results evidence that the commonly used CO2-equivalent with its GWP100 does not represent the atmospheric responses, and particularly the warming of the exemplary short-lived HFC. Through the literature review, however, we identify many other metrics available that could be applied for f-gases, and particularly GWP* is recommended to examine in future works. In summary, the paper offers insights into which metrics can best help to identify the effects of f-gases in terms of reducing global warming in a rapid timeframe, and how CO2-equivalents should not be used as proxy for atmospheric warming in policy discussions.